(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
This quantitative study sought to explore the challenges that primary school teachers experience in teaching Social Studies as an integrated subject. Data for the study was gathered using a questionnaire sent to 178 practising teachers from urban and rural school and interviews with ten lecturers from four teachers’ training colleges. Findings suggest that teachers experience several challenges such as inadequate grounding to enable them to effectively deliver the subject, a limited conception of curriculum integration and lack of resources to facilitate implementation of the approach. The study recommends that teachers training colleges and universities should evaluate their current Social Studies courses so as to equip trainees with knowledge and skills to handle the subject. Alos, professional development opportunities should be regularly availed to so that teachers can keep abreast with developments in the subject.